Tourists Intention to Choose Halal Restaurants in Malaysia: A Conceptual Paper - Mohamed, Muharis; Patwary, Ataul Karim; Abumandil, Mohanad S.S. (South Asian Journal of Social Sciences and Humanities, 2021)
Muslims around the world are concerned about the halal concept. Consumers are becoming more aware of health, making halal food interest in today’s business. Today has huge potential in capturing non-Muslim as the target market. Halal food has gone far beyond the values of only about religion. The restaurant industry must explore the concept of halal in more detail. In the restaurant industry, halal represents hygiene, cleanliness and the quality of the food consumed. This study examines the influence of the halal concept on customers’ intention in choosing a restaurant as their preferred eating place. By using the intercept survey method, data were collected in Klang Valley, Malaysia. The present study confirms previous findings on the relationship between attitudes towards halal intention. Customers with high halal attitudes concern are more willing to purchase from halal-certified restaurants. The present study also found a positive and significant relationship between halal awareness and intention to choose Halal restaurants among tourists.